2018
DOI: 10.1158/1078-0432.ccr-17-1932
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Exploration of Cancer Stem Cell Marker Voltage-Dependent Calcium Channel α2δ1 Subunit-mediated Chemotherapy Resistance in Small-Cell Lung Cancer

Abstract: Purpose: Chemoresistance in small-cell lung cancer (SCLC) is reportedly attributed to the existence of resistant cancer stem cells (CSC). Studies involving CSC-specific markers and related mechanisms in SCLC remain limited. This study explored the role of the voltage-dependent calcium channel a2d1 subunit as a CSC marker in chemoresistance of SCLC, and explored the potential mechanisms of a2d1-mediated chemoresistance and strategies of overcoming the resistance. Experimental Design: a2d1-positive cells were id… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 40 publications
3
44
0
Order By: Relevance
“…This mechanism might be involved in the maintenance of CSC property and resistance to chemotherapy. 10 , 27 In the NSCLC cell lines in this study, the increased phosphorylation level of ATM, rapid decrease in γH2AX after radiation and upregulation of DNA damage repair gene RAD51 in the CACNA2D1 -overexpressing cell line or α2δ1-high cells suggests that α2δ1 might enhance radioresistance by imparting a more efficient capacity to repair DNA damage.…”
Section: Discussionmentioning
confidence: 80%
“…This mechanism might be involved in the maintenance of CSC property and resistance to chemotherapy. 10 , 27 In the NSCLC cell lines in this study, the increased phosphorylation level of ATM, rapid decrease in γH2AX after radiation and upregulation of DNA damage repair gene RAD51 in the CACNA2D1 -overexpressing cell line or α2δ1-high cells suggests that α2δ1 might enhance radioresistance by imparting a more efficient capacity to repair DNA damage.…”
Section: Discussionmentioning
confidence: 80%
“…Many studies showed an expression of α2δ1 subunit in different types of malignancies such as pancreatic [21], ovarian [22], and lung tumors [14] and demonstrated a potential resistance to chemotherapy and may carry bad prognosis. Han et al as well identified a subpopulation of TICs expressing α2δ1 subunit, which is essential for the activation of calcium influx that controls the TIC ability of HCC by an antibody against Hep-12 cells [23].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors showed that there were other types of cancer that contain α2δ1+ cells such as small-cell lung cancer, laryngeal squamous cell carcinoma, and gastric cancer, with nearly the same stem cell-like properties [12], resistant to chemotherapy [13], and overexpression of ERK1/2 [14]. Also, they showed that inhibition of α2δ1 may serve as a new promising therapeutic target for these CSCs [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Other types of cancer also contain a subset of α2δ1+ cells (small-cell lung cancer, laryngeal squamous cell carcinoma and gastric cancer), showing not only the same stem cell-like properties [197], but also the same chemoresistant phenotype [198] and overexpression of ERK1/2 [199]. In all cases, inhibition of α2δ1 has been proposed as a new promising therapeutic target for CSCs, including HCC CSCs [197][198][199][200].…”
Section: Mechanisms Of Resistance To Therapy Of Cscsmentioning
confidence: 99%